Modification of Traditional Tractor-Drawn Seed Drill for Arid Region Crops - Singh, A.K.; Mishra, Dinesh; Gautam, Prem Veer; Poonia, Surendra; Jain, Dilip (Annals of Arid Zone, 2022)
Time of sowing has a dominant effect on the germination of seeds and growth. The establishment of desired seed population is probably the most critical phase in the life of the crop. The role of the seed drill to provide a link between seed and soil is very important. Before 1960, the traditional methods followed for sowing of seeds were hand broadcasting, opening furrows by the wooden plough and dropping seeds by hand in the furrows, or dropping seeds in the furrows through the bamboo tube attached to the wooden plough. These methods did not uniformly distribute or accurately place the seeds at the desired depth leading to reduced plant population and hence resulting in poor yield. The more precise the sowing operation, the better the quality of crop harvested. Precision sowing reduces seed scattering and excessive use of seeds due to uniform distribution of seeds and by preventing the seed from bouncing in the furrow, which facilitates drill calibration based on the number of seeds to be placed along a unit length of the row (Gautam et al., 2019). Uniform germination and growth of plants make the subsequent operations, such as weeding and harvesting, easy with low costs (Singh and Yadav, 2014; Tayade, 2018).